2018
DOI: 10.1159/000491402
|View full text |Cite
|
Sign up to set email alerts
|

MACUSTAR: Development and Clinical Validation of Functional, Structural, and Patient-Reported Endpoints in Intermediate Age-Related Macular Degeneration

Abstract: Purpose: Currently, no outcome measures are clinically validated and accepted as clinical endpoints by regulatory agencies for drug development in intermediate age-related macular degeneration (iAMD). The MACUSTAR Consortium, a public-private research group funded by the European Innovative Medicines Initiative intends to close this gap. Procedures: Development of study protocol and statistical analysis plan including predictive modelling of multimodal endpoints based on a review of the literature and expert c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 55 publications
0
86
0
1
Order By: Relevance
“…Moreover, Sauer et al revealed that a subset of elderly "healthy" eyes shows subtle signatures indicative of AMD in fluorescence lifetime imaging ophthalmoscopy [53]. Accordingly, additional longitudinal follow-up will be needed to evaluate the genuine performance of these functional tests as intended for example by the MACUSTAR consortium [54]. In the absence of longitudinal data, however, employed means for classification are in accordance with current gold standards and published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sauer et al revealed that a subset of elderly "healthy" eyes shows subtle signatures indicative of AMD in fluorescence lifetime imaging ophthalmoscopy [53]. Accordingly, additional longitudinal follow-up will be needed to evaluate the genuine performance of these functional tests as intended for example by the MACUSTAR consortium [54]. In the absence of longitudinal data, however, employed means for classification are in accordance with current gold standards and published literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, more research is warranted, and a longitudinal follow-up will be needed to evaluate the performance of these functional tests as intended, for example, by the MACUSTAR consortium. 47…”
Section: Discussionmentioning
confidence: 99%
“…In the longitudinal part, a group of iAMD participants (target n = 600: n = 150 from the cross-sectional part, and n = 450 additional subjects) as well as the participants with early AMD (target n = 50, recruited in the cross-sectional part) are followed up for a 3-year period. The rationale of the study and the justification for the sample size have been described previously [18]. The MACUSTAR clinical study is conducted, analyzed, and reported according to current international laws and regulations and in compliance with regulatory requirements in all participating countries and the standards of good clinical practice according to the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use.…”
Section: Methodsmentioning
confidence: 99%
“…Fundus imaging including OCT, CFP, and scanning laser ophthalmoscopy (see study schedule, Table 3) are recommended to be performed next, followed by two examinations that require prior dark adaptation (5 min for mesopic fundus-controlled perimetry [also called microperimetry], additional 30 min for scotopic testing). Details on these examinations performed have been described previously [18]. All images are acquired by certified staff and evaluated centrally by trained personnel at the central reading center.…”
Section: Study Proceduresmentioning
confidence: 99%